2019
DOI: 10.1186/s12885-019-6299-4
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal associations between BMI change and the risks of colorectal cancer incidence, cancer-relate and all-cause mortality among 81,388 older adults

Abstract: BackgroundIt remains controversial whether weight change could influence the risks of colorectal cancer (CRC) and mortality. This study aimed to quantify the associations between full-spectrum changes in body mass index (BMI) and the risks of colorectal cancer (CRC) incidence, cancer-related and all-cause mortality among midlife to elder population.MethodsA total of 81,388 participants who were free of cancer and aged 55 to 74 years from the Prostate, Lung, Colorectal, and Ovarian (PLCO) screening program were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 37 publications
2
22
0
1
Order By: Relevance
“…complete-case regression analyses), with preexisting illness at baseline (including history of CHD, CHF, stroke, COPD or cancer), or with the highest weight variability; 2) we repeated the main analysis separately in each cohort; 3) we used the change in BMI relative to baseline BMI as the exposure variable (percent change of BMI) to evaluate the corresponding risks. Percent change of BMI was calculated as (last time BMI –baseline BMI)/baseline BMI [47] . Furthermore, subgroup analyses were conducted to evaluate whether the relationship between different BMI trajectories and outcomes differed by age (<60 or >=60 years), sex, race (white or non-white), smoking status (never, current or former smokers) and baseline BMI (normal, overweight or with obesity).…”
Section: Methodsmentioning
confidence: 99%
“…complete-case regression analyses), with preexisting illness at baseline (including history of CHD, CHF, stroke, COPD or cancer), or with the highest weight variability; 2) we repeated the main analysis separately in each cohort; 3) we used the change in BMI relative to baseline BMI as the exposure variable (percent change of BMI) to evaluate the corresponding risks. Percent change of BMI was calculated as (last time BMI –baseline BMI)/baseline BMI [47] . Furthermore, subgroup analyses were conducted to evaluate whether the relationship between different BMI trajectories and outcomes differed by age (<60 or >=60 years), sex, race (white or non-white), smoking status (never, current or former smokers) and baseline BMI (normal, overweight or with obesity).…”
Section: Methodsmentioning
confidence: 99%
“…Twenty-nine studies examined change in weight; 17 of 29 studies reported % change and six studies examined change in BMI. Nineteen studies were conducted in the USA [4,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35], nine in Europe [36][37][38][39][40][41][42][43][44], three in Australia [6,45,46] and four in Asia [47-50]. Follow-up duration ranged from two [20] to 20 years [39], and participants were aged between 65 and 99 years.…”
Section: Study Characteristicsmentioning
confidence: 99%
“… 20 Other evidence supporting our finding comes from Li et al, who found that for each 5% decrease in BMI, there was a 27% increase in overall mortality; they concluded that increased mortality was linked to lower BMI. 21 In contrast, Shaukat et al's study on CRC mortality found that a higher BMI was related to increased mortality. 22 These findings may guide the MDT and improve a patient's general health by the inclusion of not only physicians but also nurses and nutritionists in the MDT.…”
Section: Discussionmentioning
confidence: 92%